2016
DOI: 10.1007/s00005-016-0409-7
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–Mesenchymal Transition in Chronic Rhinosinusitis: Differences Revealed Between Epithelial Cells from Nasal Polyps and Inferior Turbinates

Abstract: The pathogenesis of chronic rhinosinusitis (CRS) remains unclear to date. The tissue remodeling in nasal polyps may be the result of inflammatory mediators and may involve epithelial-mesenchymal transition (EMT) and EMT-associated features such as cell motility in nasal epithelial cells (NECs). We determined whether NEC in nasal polyps of CRS already display features of EMT in vivo or respond with EMT to growth factor stimulation in vitro. Nasal polyp tissues expressed both epithelial and mesenchymal markers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 43 publications
6
51
0
1
Order By: Relevance
“…Soon afterwards, studies revealed that the enhanced expression of miR-21 is involved in the progression of lung fibrosis, and TGF-β1 plays an important role in mediating the increased miR-21 expression [34, 44]. Because TGF-β1, a well-known stimulator of EMT, induces the transition of epithelial cells into myofibroblasts, contributing to tissue remodeling and the pathogenesis of CRSwNP [15, 17], the induction of miR-21 by TGF-β1 suggests that miR-21 may have a potential role in the pathogenesis of CRSwNP. The related literature [15, 17, 34, 44] was consistent with our findings.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soon afterwards, studies revealed that the enhanced expression of miR-21 is involved in the progression of lung fibrosis, and TGF-β1 plays an important role in mediating the increased miR-21 expression [34, 44]. Because TGF-β1, a well-known stimulator of EMT, induces the transition of epithelial cells into myofibroblasts, contributing to tissue remodeling and the pathogenesis of CRSwNP [15, 17], the induction of miR-21 by TGF-β1 suggests that miR-21 may have a potential role in the pathogenesis of CRSwNP. The related literature [15, 17, 34, 44] was consistent with our findings.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…TGF-β1 initiates EMT signaling by binding to type I and type II receptor serine/threonine kinase on the cell surface [59], regulating gene expression by receptor-mediated activation of Smad (R-Smad) transcription factors [60]. Despite contradictory reports about TGF-β1 expression in CRSwNP, its unclear pathophysiology, and underlying mechanisms of nasal polyp formation, TGF-β1 is considered to be a well-known master player in fibrosis and EMT, inducing the transition of epithelial cells into myofibroblasts and contributing to tissue remodeling and the pathogenesis of CRSwNP [15, 17, 61, 62]. Our tissue experiments showed that mRNA and protein expression of TGF-β1 was strongly increased in CRSwNP.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In an animal model of pancreatic cancer, ADH‐1 showed the inhibitory effect against tumour growth and metastasis . Importantly, a phase I/II clinical trial has shown combination of ADH‐1 and melphalan could suppress tumour growth in patients with locally advanced melanoma . Furthermore, ADH‐1 was evaluated to be well tolerable both in animal models and humans .…”
Section: Discussionmentioning
confidence: 99%
“…73 Importantly, a phase I/II clinical trial has shown combination of ADH-1 and melphalan could suppress tumour growth in patients with locally advanced melanoma. 74 Furthermore, ADH-1 was evaluated to be well tolerable both in animal models and humans. 75,76 However, according to current clinical evidences, the clinical significance of Ncadherin still was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that epithelial–mesenchymal transition (EMT); which is integral to development and can be reactivated in wound healing, fibrosis, and cancer progression, may also be involved in tissue remodeling in CRSwNP patients . Although chronic EMT is characterized by an expanded basement membrane (BM), changes in the expression of tissue remodeling‐related molecules including matrix metalloproteinase(MMP) family members and tissue inhibitor of metalloproteinases (TIMPs), soluble growth factors or cytokines including transforming growth factor‐β (TGF‐β) family members, T‐helper 2 (Th2)‐type cytokines, and inflammatory cells such as eosinophils, the mechanisms involved in ECM in CRSwNP are not fully understood.…”
mentioning
confidence: 99%